Document Digitization for Reducing Paper Consumption in Small Family Businesses - Atanase, Florina; Gologan, Mihaela (European Journal of Sustainable Development, 2025)
The growing importance of sustainability has influenced the country's legislators to establish new environmental rules. Romania started this lane by supervising the recycling, yet with limited interest in reducing consumption. Without having any external constraints, several small businesses, especially family businesses, understand the need to contribute to environment maintenance from a competitiveness point of view. The research completed and published until 2025 are concentrating on Sustainable Development Goals (SDG), Corporate Social Responsibility (CSR) general impact on business. Despite the low volume contribution of small businesses to global paper consumption, they are no less important. This paper initiates the analysis of factors contributing to a family business's decision to start document digitisation and the obstacles they face during the process. The data acquired from directors' interviews establish the ground for future empirical studies that could confirm the elements contributing to organisational readiness to change. The findings can be replicated in similar family businesses to achieve economic and environmental objectives. Keywords: documents digitization, family business, paper consumption, small business, organizational readiness for change, ORC